STRATEGIES FOR IMPLEMENTHING THE HIDDEN CURRICULUM IN THE DEVELOPMENT OF RELIGIOUS AND MORAL VALUES IN EARLY CHILDREN - Latifah, Ibdaul (THUFULA, 2024)
The aim of this research is to identify the existence of a hidden curriculum in early childhood learning in developing aspects of religious and moral values as well as teacher strategies in implementing the hidden curriculum at PAUD Siti Rahma Pabelan. Data collection procedures use interviews, observation and documentation. Interviews were conducted with the school principal and teacher council at PAUD Siti Rahma Pabelan using structured interview techniques. Observation sheets are used to discover hidden curriculum in learning. Documentation is used to identify between the core curriculum and the hidden curriculum. Data analysis was carried out by collecting data from interviews, observation sheets and documentation, then reducing it, presenting it and drawing conclusions. The results of this research explain that there are several hidden curriculum in the learning process which are divided into programmed activities, non-programmed activities and incidental activities. The hidden curriculum is implemented in various ways, including storytelling, playing, habituation, and reward and punishment. The novelty of this research is describes activities regarding the hidden curriculum in early childhood institutions and strategies for implementing it so that teachers better understand and comprehend the importance of the hidden curriculum for the development of children’s religious and moral values.